Unusual Cause of Massive Upper Gastrointestinal Bleeding: A Pancreatic Arteriovenous Malformation - Arora, Anil; Tyagi, Pankaj; Kirnake, Vijendra; Singla, Vikas; Sharma, Praveen; Bansal, Naresh; Ghuman, Samarjit Singh; Jain, Deepali; Kumar, Ashish (JOP. Journal of the Pancreas, 2013)
Context Upper gastrointestinal bleeding is one of the most common emergencies in gastroenterology. The common causes of the upper gastrointestinal bleeding include peptic ulcer disease, gastric erosive mucosal disease and portal hypertension. Gastrointestinal arteriovenous malformation is a less common cause of gastrointestinal bleeding and these arteriovenous malformation are most commonly located in the large and small intestine. Pancreatic arteriovenous malformation is a rare condition in which there is tumor-like formation or vascular anomaly built up via an aberrant bypass anastomosis of the arterial and venous systems in the pancreas. Splenic artery is most commonly involved (42%), followed by gastroduodenal artery (22%) and small pancreatic arteries (25%). Clinically it may present as gastrointestinal hemorrhage which is occasionally fatal. Other presentations are abdominal pain, pancreatitis, duodenal ulcer, jaundice, and portal hypertension. Case report We present a rare case of pancreatic arteriovenous malformation presenting as massive upper gastrointestinal bleeding. Conclusion Since early surgery is a life saving treatment for such cases, hence, a high index of suspicion should be maintained especially when massive bleeding is detected from the medial wall of second part of duodenum. Image: Gross specimen of the pancreatic arteriovenous malformation.